2003
DOI: 10.1246/cl.2003.394
|View full text |Cite
|
Sign up to set email alerts
|

GHz Range Absorption Properties of α-Fe/Y2O3 Nanocomposites Prepared by Melt-spun Technique

Abstract: Nanocomposite materials of α-Fe/Y2O3 prepared by melt-spun technique exhibited good electromagnetic wave absorption properties (RL<−20 dB) in a 2.0-3.5 GHz range as absorbers with thickness ranging from 3 to 5 mm, and a minimum reflection loss of −36 dB was obtained at 2.6 GHz with an absorber thickness of 4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 9 publications
0
55
0
Order By: Relevance
“…: +81 6 6879 4209; fax: +81 6 6879 4209. Sugimoto et al [2,3] have reported the ␣-Fe/SmO composite powders which possess good microwave absorption properties (RL <−20 dB) in 0.73-1.30 GHz range, and good microwave absorption properties of the ␣-Fe/Y 2 O 3 nanocomposite at 2.0-3.5 GHz were demonstrated by our previous study [4]. In these works, both nanocomposite materials were prepared by the hydrogen disproportionation process for rareearth intermetallic compounds, Sm 2 Fe 17 and Y 2 Fe 17 , followed by the oxidation for forming the rare-earth oxides as insulators, SmO or Y 2 O 3 , which increase the electrical resistivity owing to their effective isolation for ␣-Fe particles.…”
Section: Introductionmentioning
confidence: 58%
“…: +81 6 6879 4209; fax: +81 6 6879 4209. Sugimoto et al [2,3] have reported the ␣-Fe/SmO composite powders which possess good microwave absorption properties (RL <−20 dB) in 0.73-1.30 GHz range, and good microwave absorption properties of the ␣-Fe/Y 2 O 3 nanocomposite at 2.0-3.5 GHz were demonstrated by our previous study [4]. In these works, both nanocomposite materials were prepared by the hydrogen disproportionation process for rareearth intermetallic compounds, Sm 2 Fe 17 and Y 2 Fe 17 , followed by the oxidation for forming the rare-earth oxides as insulators, SmO or Y 2 O 3 , which increase the electrical resistivity owing to their effective isolation for ␣-Fe particles.…”
Section: Introductionmentioning
confidence: 58%
“…To compare with ferrites, the matching thickness (d m ) for Y 2 Fe 17 /a-C composite absorbers thinned down about 20-40% in the same frequency range [12,13], since the Y 2 Fe 17 /a-C resin composite possess the higher µ r value than ferrites in the above frequency range. Furthermore, the effective absorption (RL < −20 dB) for the Y 2 Fe 17 /a-C resin composite was obtained in the range of 9-18 GHz, which is higher than that for ␣-Fe/Y 2 O 3 reported previously [8]. The natural resonance frequency f r is related to the magnetic anisotropy field H A as a below equation:…”
Section: Resultsmentioning
confidence: 78%
“…In this nanocomposite, the fine Fe particles were isolated from one another by the insulating SmO particles to effectively reduce the eddy current loss. In our previous works, the Fe electromagnetic wave absorption properties with the several GHz range [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Table 2. Comparing Fe 1−x Co x /Y 2 O 3 (x = 0.33, 0.5, 0.67) with ␣-Fe/Y 2 O 3 sample [9], the minimum reflection point shifted to the higher frequency, and moreover the elec- tromagnetic wave absorption bandwidth, with RL < −20 dB, was broadened to larger frequency range with increasing the amount of Co (see Fig. 5).…”
Section: Resultsmentioning
confidence: 93%
“…We have found the ␣-Fe/Y 2 O 3 composite powders prepared via such melt-spun process show good electromagnetic wave absorption properties in the 2.0-3.5 GHz range because of the fine grain size of ␣-Fe (∼20 nm) [9].…”
Section: Introductionmentioning
confidence: 93%